Once upon a time in Russia : the rise of the oligarchs -- a true story of ambition, wealth, betrayal, and murder - Mezrich, Ben, 1969- (Atria Books, 2015)
This book offers a gripping and shocking insight into the lives of Russia's most famous oligarchs from New York Times bestselling author of The Accidental Billionaires and Bringing Down the House. 'Once upon a time in Russia' is the story of modern day Russia through the eyes of some of the most powerful and wealthy people in the world: the oligarchs. The story starts in the early 1990s with the formation of the huge oil company Sibneft owned by Roman Abramovich (with help from Boris Berezovsky), and takes the reader right through from Boris Yeltsin's resignation on New Year's Eve of the millennium, Putin's rise to power and Alexander Litvinenko's assassination to Berezkovsky's court case against Abramovich in 2011, which was the largest civil court case in British legal history. Told in an intimate narrative voice that makes you feel part of the action, but at an exhilarating pace that is typical of Mezrich, 'Once upon a time in Russia' is his most hard-hitting and pertinent work yet.